Spectral imaging of the Central Molecular Zone in multiple 3-mm molecular lines - Jones, P.; Burton, M.; Cunningham, M.; Requena-Torres, M.; Menten, K.; Schilke, P.; Belloche, A.; Leurini, S.; Martin-Pintado, J.; Ott, J.; Walsh, Andrew (Oxford University Press, 2012)
We have mapped 20 spectral lines in the Central Molecular Zone (CMZ) around the Galactic Centre, emitting from 85.3 to 93.3 GHz. This work used the 22-m Mopra radio telescope in Australia, equipped with the 8-GHz bandwidth University of New South Wales-Mopra Spectrometer (UNSW-MOPS) digital filter bank, obtaining ~ 2 km s-1 spectral and ~ 40 arcsec spatial resolution. The lines measured include emission from the c-C3H2, CH3CCH, HOCO+, SO, H13CN, H13CO+, SO, H13NC, C2H, HNCO, HCN, HCO+, HNC, HC3N, 13CS and N2H+ molecules. The area covered is Galactic longitude -0°.7 to 1°.8 and latitude -0°.3 to 0°.2, including the bright dust cores around Sgr A, Sgr B2, Sgr C and G1.6-0.025. We present images from this study and conduct a principal component analysis on the integrated emission from the brightest eight lines. This is dominated by the first component, showing that the large-scale distribution of all molecules is very similar. We examine the line ratios and optical depths in selected apertures around the bright dust cores, as well as for the complete mapped region of the CMZ. We highlight the behaviour of the bright HCN, HNC and HCO+ line emission, together with that from the 13C isotopologues of these species, and compare the behaviour with that found in extragalactic sources where the emission is unresolved spatially. We also find that the isotopologue line ratios (e.g. HCO+/H13CO+) rise significantly with increasing redshifted velocity in some locations. Line luminosities are also calculated and compared to that of CO, as well as to line luminosities determined for external galaxies.